![f(x)=(3x)/(4-x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/u6sck3wqumdwfhy6o1zptfygo1yg9foqyt.png)
First Method: Using Graph
Finding the limits as x approaches infinity and negative infinity is one way to solve this problem. As x reaches infinity, simply follow the graph line (colored purple) to the far right to find its limit. If we trace it, we can see that the Y value never exceeds -3 (orange), indicating that the limit is equal to -3 as x approaches infinity. You'd do the same with negative infinity, the limit is -3. We may now say the following:
![\lim_(x \to \infty) ((3x)/(4-x))=-3 \\ \lim_(x \to -\infty) ((3x)/(4-x))=-3](https://img.qammunity.org/2022/formulas/mathematics/high-school/v8rj7up0q9cng0vxjimk6jmsed0z6p8vhh.png)
And that's the answer to your question.
Second Method: Using Mathematics
I'm not sure if this solution is suitable for your stage, but you can solve this problem using L'Hopital's rule:
![\lim_(x \to \infty) ((3x)/(4-x)) =(\infty)/(-\infty)\\=^L \lim_(x \to \infty) ((3)/(-1)) = -3\\\\ \lim_(x \to- \infty) ((3x)/(4-x)) =(-\infty)/(\infty)\\=^L \lim_(x \to- \infty) ((-3)/(1)) = -3](https://img.qammunity.org/2022/formulas/mathematics/high-school/z0d0go3732resenzag1hwx8osinvxrag52.png)
Graphed by: Desmos